2018
DOI: 10.3389/fmicb.2018.00264
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Molecular Mechanism of the Transcriptional Regulation of amtB Operon in Streptomyces coelicolor

Abstract: In Streptomyces coelicolor, amtB transcription is promptly regulated by the global nitrogen regulator GlnR. Although the GlnR binding cis-element has been characterized in amtB promoter, consisting of three GlnR boxes of a3-b3, a1-b1, and a2-b2, its role in GlnR-mediated transcriptional regulation remains unclear. Here, we showed that GlnR had different binding affinity against each pair of GlnR binding sites in amtB promoter (i.e., a3-b3, a1-b1, and a2-b2 sites), and GlnR was able to bind a3-b3 and a1-b1, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 34 publications
(54 reference statements)
2
13
0
Order By: Relevance
“…Of the three GlnR sites of amtB , a2b2 displays the fewest conserved nt, and this lack of conservation may be more tolerated by MtrA than by GlnR. Our data showing binding of a1b1 and a3b3, but not a2b2, by GlnR is consistent with a previous report (Li et al , ). Collectively, our data indicated that MtrA recognizes all three GlnR boxes upstream of amtB , whereas GlnR recognizes only two of three.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Of the three GlnR sites of amtB , a2b2 displays the fewest conserved nt, and this lack of conservation may be more tolerated by MtrA than by GlnR. Our data showing binding of a1b1 and a3b3, but not a2b2, by GlnR is consistent with a previous report (Li et al , ). Collectively, our data indicated that MtrA recognizes all three GlnR boxes upstream of amtB , whereas GlnR recognizes only two of three.…”
Section: Resultssupporting
confidence: 92%
“…Shifting of the a3b3 probe was also detected with GlnR (Fig. D and E), consistent with a previous report (Li et al , ) and indicating that a3b3 is a genuine GlnR box. To validate the role of the conserved nucleotides in a3b3, we performed EMSAs using oligonucleotides with point mutations in the repeat motifs of a3b3; such mutated fragments can serve as negative controls and demonstrate the specificity of MtrA binding.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Recently, it was experimentally demonstrated that MtrA binds to one of the three putative GlnR binding sequences upstream of the amtB-glnK-glnD cluster (Zhu et al, 2019). Previously, three putative GlnR binding sites (named a1-b1, a2-b2, and a3-b3), each consisting in two binding repeats had been identified in the amtB promoter region (Wang et al, 2012;Li et al, 2018). More recently, Zhu et al (2019) showed that the developmental regulator MtrA recognizes the a3-b3 binding sequence which also binds GlnR efficiently.…”
Section: Role Of the Two Components System Mtrab In Nitrogen Metabolimentioning
confidence: 99%